The prevalence of metabolic dysfunction-associated steatotic liver disease (MASLD)-related advanced fibrosis and cirrhosis in the United States population utilizing AGILE 3 + and AGILE 4 scores: analysis of the NHANES 2017–2018 cycle - Alkhouri, Naim; Almomani, Ashraf; Le, Phuc; Payne, Julia Y.; Asaad, Imad; Polanco, Prido; Leff, Phillip; Kumar, Prabhat; Noureddin, Mazen (BMC gastroenterology, 2024)
Background Studies attempted to estimate MASLD-related advanced fibrosis (AF) and cirrhosis (MC) prevalence utilized tests with low positive predictive value (PPV) which overestimates prevalence. AGILE3 + and 4 scores were developed to increase the PPV of both; respectively. In this study, we used these scores to assess the prevalence of AF and MC. Methods Participants aged ≥ 18 years with VCTE exam in the NHANES 2017–2018 cycle were included. We excluded pregnant women, patients with excessive alcohol intake, hepatitis B/C, and ALT or AST > 500 IU/L. MASLD was defined with CAP score > 248 dB/m. MASLD subjects with AGILE 3 + score of ≥ 0.68 and AGILE 4 score of ≥ 0.57 were considered to have advanced fibrosis and cirrhosis; respectively. AGILE 3 + of 0.45–0.67 and AGILE 4 of 0.25–0.57 were grey zone, whereas AGILE 3 + < 0.45 and AGILE 4 < 0.25 were considered a rule-out. Results 1244 subjects were included in the final analysis. The Median age was 53 (51.4–54.6) years, 55.6% were male, median BMI was 33.8 kg/m2 and 41.1% had T2DM. Based on AGILE 3+, 80.3% of the MASLD population were at low risk for AF and 11.5% were in grey zone. The prevalence of AF due to MASLD was 8.1% corresponding to 4.5 million Americans. Based on AGILE 4 score, 96.5% of the MASLD population were at low risk for cirrhosis and 2.4% were in the grey zone. The prevalence of MASLD-cirrhosis was 1.1% corresponding to 610,000 Americans. Conclusion Our results suggest that approximately 4.5 million people in the U.S. have AF and 0.6 million have cirrhosis due to MASLD.